2017
DOI: 10.5435/jaaos-d-15-00447
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Restoration Techniques for the Patellofemoral Joint

Abstract: Symptomatic osteochondral lesions of the patellofemoral joint are clinically challenging to manage because of the limited healing potential of articular cartilage; the complex morphology of the patellofemoral joint; the heterogeneity of the articular surface between patients; and high stresses across the joint, which can be altered by malalignment, tilt, or maltracking. Indications for surgery include traumatic lesions, osteochondritis dissecans, and high-grade chondromalacia in association with persistent pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 26 publications
0
44
0
2
Order By: Relevance
“…As a result of this complexity, inferior outcomes have been reported with the treatment of symptomatic large patellofemoral lesions when compared with tibiofemoral cartilage treatments. 12,24 In addition, clinical studies, especially clinical trials, very often focus on the tibiofemoral joint, and the literature on cartilage restoration in the patellofemoral joint is much more limited. 24,40,80 For those reasons, significant debate remains regarding the indications and specifics of each technique for the surgical treatment of patellofemoral chondral defects.…”
mentioning
confidence: 99%
“…As a result of this complexity, inferior outcomes have been reported with the treatment of symptomatic large patellofemoral lesions when compared with tibiofemoral cartilage treatments. 12,24 In addition, clinical studies, especially clinical trials, very often focus on the tibiofemoral joint, and the literature on cartilage restoration in the patellofemoral joint is much more limited. 24,40,80 For those reasons, significant debate remains regarding the indications and specifics of each technique for the surgical treatment of patellofemoral chondral defects.…”
mentioning
confidence: 99%
“…Existe poco escrito en la literatura sobre el acceso a la superficie articular de la patela para el manejo de lesiones condrales y la mayoría de las referencias son cirugías abiertas (6,10,12,13,18,19) . Pocas son las técni-cas completamente artroscópicas que existen reportadas.…”
Section: Discussionunclassified
“…El tratamiento de las lesiones condrales en patela suele ser difícil y controvertido. Dentro de las opciones disponibles se encuentran las microfracturas (7)(8)(9) , las cuales tienen la desventaja de ser un procedimiento técnicamente difícil por el ángulo de visualización y el acceso a las lesiones condrales en patela (10) ; además, el hecho de utilizar un microfracturador angulado no permite la transmisión de las cargas adecuadamente para llegar al hueso subcondral, reportándose tasas de revisión de hasta un 31% a 5 años (9) . El traslado osteocondral también resulta ser una técnica difícil en patela, ya que conlleva en primera instancia realizar una artrotomía y liberación retinacular para evertir la patela y acceder a la superficie articular (11) , además de que el autoinjerto femoral es estructuralmente diferente del cartílago patelar nativo adyacente, por lo que no suele otorgar adecuada congruencia (10) , además de ocasionar una alta tasa de rigidez postoperatoria.…”
Section: Introductionunclassified
“…OAT is a technique in which healthy hyaline cartilage from a non-weight bearing region of the knee is transplanted to a focal chondral defect to restore function and provide pain relief, and this has been shown to be a successful way of managing chondral or osteochondral defects of the patella. 2,21 However, the particular biomechanical properties of the patella pose a unique challenge to restoring its articular surface's structure and function by way of OAT, as studies have shown that it tends to achieve more favorable outcomes when used to treat condylar lesions compared with those of the patellofemoral joint. 22 In addition, the OAT technique itself presents as a unique approach, regardless of the compartment in which it is applied.…”
Section: Osteochondral Autograft Transplantation In the Patella Overviewmentioning
confidence: 99%
“…The goal of patellofemoral cartilage restoration procedures is to impart symptomatic relief and improve quality of life by repairing the articular cartilage surface and any comorbid malalignment or maltracking. 2,5 The purpose of this article is to discuss two common cartilage restoration procedures, microfracture and osteochondral autograft transplantation (OAT), used when treating chondral lesions of the patellofemoral joint.…”
mentioning
confidence: 99%